Entry Mechanisms into the Belgian Synthetic Drugs Market - De Seranno, Sophia (Journal of drug issues, 2025)
Organised crime groups prefer existing ties, such as family and friendship, to maximise trust. However, they might also win from a certain degree of heterogeneity. External individuals might add value in the form of skills, expertise or money. Accordingly, including suitable co-offenders is an important activity for the organised crime group. This article studies the entry mechanisms of individuals into the synthetic drugs market in Belgium, namely by gaining insight into the factors and mechanisms introducing people into this market. Interviews with 29 inmates detained for their involvement in the production and/or trafficking of synthetic drugs in Belgium revealed that: (1) poly drug supply markets exist in Belgium; (2) financial reasons to enter the market are common; and (3) there are six different entry mechanisms, in which trust is crucial, namely criminal family ties, criminal friends, drug use, earlier time in prison, outlaw motorcycle gang membership, and criminal professional ties.